Maintaining a minority language : a case study of Hispanic teenagers - Gibbons, John, 1946- (Multilingual matters (Series), 2004)
Based on research carried on in Sydney, New South Wales, this volume evaluates different levels of bilingual proficiency and explores the factors which mitigate towards or against the development of minority language skills.